Fuzzy Parabola - Ghosh D.; Chakraborty D. (My University, 2025)
This chapter attempts to construct fuzzy parabola in detail. Depending on the available information about the fuzzy parabola, two different formulations are discussed. Construction of the membership functions of fuzzy parabolas are detailed with numerical illustrations. Different results and interrelations on the attributes of fuzzy parabolas are presented. © 2019, Springer Nature Switzerland AG.